Effects of Anticholinergic Drugs on Visual Acuity of Patients with Tracheal Intubation under General Anesthesia. (20th June 2022) - Song, Jinmei; Shen, Wenchao; Cheng, Yi; Zheng, Yunhui
Abstract : Background . General anesthesia (GA) is the core means of surgical intervention, mainly used for analgesia and anxiety relief. Therefore, it is necessary to understand the laboratory and clinical research results during induction of GA. Penehyclidine hydrochloride (PHCD) combined with atropine sulfate (Atr) has the potential to induce GA. However, the role of PHCD combined with Atr during tracheal intubation under GA remains unclear. Objective . The research is aimed at exploring the effects of preoperative PHCD or Atr on adverse reactions (ARs) in patients during tracheal intubation under general anesthesia (GA). Methods . This study retrospectively enrolled 473 patients who underwent surgery under GA induction and divided them into a research group (n = 234 ) and a control group (n = 239 ) according to preoperative use of PHCD (with or without). Both groups of patients were given Atr postoperatively and nursing intervention. Anesthesia-related indexes, ARs, and hemodynamics were observed and compared between the two groups. Results . There were no significant differences in anesthesia-related indexes and hemodynamics between the research group and the control group. The incidence of blurred vision and diplopia in the research group was higher than that in the control group. Conclusion . Preoperative PHCD combined with postoperative Atr should be avoided in clinical practice, or Atr rather than PHCD should be used preoperatively, so as to reduce the occurrence of blurred vision, diplopia, and other ARs.